THE INTERPRETATION OF MIM IN THE FALA RAHA CULTURE OF THE TERNATE COMMUNITY - Jerry Dounald Rahajaan (Universitas Negeri Makassar, 2021)
The concept of Fala Raha that exists in Ternate society (North Maluku), has a high understanding of meaning in their cultural life. This philosophical meaning can be interpreted scientifically and conceptually into the meaning of MIM in the understanding of Islamic religion.The concept of Fala Raha which is interpreted in the understanding of MIM in Islamic religion, is embodied in the self concept (Fangare). The embodiment of MIM in the self-concept (Fangare) for Ternate society, is an acknowledgment of the kinship that exists in their cultural structure, so that it becomes an essential life concept for Ternate society (North Maluku).